2022
DOI: 10.1155/2022/3889563
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy of Composite Medicinal Plant Extracts and Gum Arabic on Improving Postharvest Quality in Dragon Fruit

Abstract: Several natural preservative techniques including plant extracts are used to minimize postharvest losses caused by pathogens. Our recent findings elucidated that the application of crude extracts of ginger, turmeric, and “dukung anak” (Phyllanthus niruri Linn.) alone causes phytotoxicity and adversely affects the postharvest quality of dragon fruit, especially at high concentrations. This study investigated the effect of a composite coating of 10% gum arabic (GA) and crude extracts of ginger, turmeric, and “du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Interaction between treatments and storage duration on the citrus fruits showed the highest juice weight (51.73 %) was recorded in citrus fruits treated with 20% ginger extraction while the lowest juice weight (42.23 %) was recorded in fruits stored for 12 days. Our result matched (Bordoh et al, 2022) concluded that Ginger extract treatments effectively create a barrier against moisture loss, delaying dryness and fruit shrivelling , leading to fruits that maintain a substantial amount of juice.…”
Section: Juice Weight Of Citrus CV Red Blood During Storage (%)supporting
confidence: 87%
“…Interaction between treatments and storage duration on the citrus fruits showed the highest juice weight (51.73 %) was recorded in citrus fruits treated with 20% ginger extraction while the lowest juice weight (42.23 %) was recorded in fruits stored for 12 days. Our result matched (Bordoh et al, 2022) concluded that Ginger extract treatments effectively create a barrier against moisture loss, delaying dryness and fruit shrivelling , leading to fruits that maintain a substantial amount of juice.…”
Section: Juice Weight Of Citrus CV Red Blood During Storage (%)supporting
confidence: 87%
“…The purpose of this paper is to summarize the types of postharvest diseases affecting pitaya, their symptoms, the pathogens responsible for them, and the techniques used to prevent and control them (Table 2). Colletotrichum pathogen 10% GA plus 15 g•L − 1 ginger or turmeric extract [66] Colletotrichum pathogen Conventional chitosan (CC) and submicron chitosan dispersions (SCD)…”
Section: Postharvest Fungi and Diseases Of Pitayamentioning
confidence: 99%
“…Crude extracts of ginger, turmeric rhizomes, and certain medicinal herbs were found to cause deformation, contraction, and solubilization of anthracnose mycelium at appropriate concentrations; these extracts also inhibited mycelial growth and conidial germination. In addition, the addition of 10% gum arabic (GA) to ginger or turmeric extracts at high concentrations was found to be effective in deterring anthracnose on pitaya [66,84]. Microbial growth, fruit decay, water loss, and anthracnose incidence were inhibited by a 1.0% solution of submicron chitosan dispersion (SCD) with a droplet size of 600 nm and low-molecular-weight chitosan (LMWC) [67,68].…”
Section: Techniques To Prevent and Control Diseasementioning
confidence: 99%